Bahasa Inggris - Zainuri, Ach. Muhib; Asrori, Asrori; Takwim, R. N. Akhsanu; Suharto, Nugroho; Helmy, Abdullah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Tourism development is an effort to create added value in all aspects of the tourism sector, starting from facilities and infrastructure, tourist objects and attractions, and other aspects. One of the tourism developments is the Lembung Mangrove Ecotourism in Lembung Village, Galis District, Pamekasan Regency. The problem with developing Lembung Mangrove Ecotourism in Lembung Village is that it has not properly accommodated visitor needs, such as the existence of good tourist facilities. Based on this, it is necessary to develop sustainable ecotourism. The aim of this community service (CS) is to develop Lembung Mangrove Ecotourism facilities in Lembung Village so that the local economy and community empowerment increase. The types of facilities and infrastructure developed by the CS Polinema team for the community partnership scheme at CS locations are in the form of science and technology diffusion of appropriate technological equipment, namely: deep fat frying machine. The PPM results are then awarded to Tourism Awareness Group (Pokdarwis) “Sabuk Hijau”.